2023
DOI: 10.3389/fnut.2023.1197745
|View full text |Cite
|
Sign up to set email alerts
|

Association between wine consumption and cancer: a systematic review and meta-analysis

Maribel Lucerón-Lucas-Torres,
Iván Cavero-Redondo,
Vicente Martínez-Vizcaíno
et al.

Abstract: BackgroundAlcohol consumption is related to the risk of developing different types of cancer. However, unlike other alcoholic beverages, moderate wine drinking has demonstrated a protective effect on the risk of developing several types of cancer.ObjectiveTo analyze the association between wine consumption and the risk of developing cancer.MethodsWe searched the MEDLINE (through PubMed), Scopus, Cochrane, and Web of Science databases to conduct this systematic review and meta-analysis. Pooled relative risks (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 123 publications
0
1
0
Order By: Relevance
“…Reading the article by Luceron-Lucas-Torres et al ( 1 ) we were quite surprised to find that in the abstract the authors drew conclusions that are not supported by data reported in the paper.…”
mentioning
confidence: 90%
“…Reading the article by Luceron-Lucas-Torres et al ( 1 ) we were quite surprised to find that in the abstract the authors drew conclusions that are not supported by data reported in the paper.…”
mentioning
confidence: 90%